Letter from Pat Russell - Pat Russell:::::: (1974)
In this August 30, 1974 letter from the California Elected Women's Association for Education and Research, Pat Russell highlights the favorable political climate for increasing women's participation in public office. She announces an October 3–4 conference in San Mateo aimed at building membership and expanding women's influence in public affairs, with workshops on issues such as education, employment, criminal justice, housing, and health. The letter encourages both women and supportive men to join CEW and continue strengthening women's political leadership.